F108. CONCURRENT USAGE OF SUBLINGUAL OXYTOCIN AND CLOZAPINE TO TREAT THE POSITIVE AND NEGATIVE SYMPTOMS WITHIN INDIVIDUALS WITH TREATMENT-RESISTANT SCHIZOPHRENIA. (9th April 2019) - Marotta, Rocco; Rowe, David; Collins, Eric; Cerrito, Brianna; O'Connell, Julianne; Garakani, Amir; Buono, Frank
Abstract: Background: The prevalence of schizophrenia in the United States ranges between 0.5% and 1%. This difficult-to-treat disorder is marked by the presentation of symptoms that are both positive (i.e. hallucinations) and negative (i.e. blunted affect), as well as disturbances in cognition and affect. Several second-generation antipsychotics (i.e. olanzapine, risperidone, etc.) have been utilized for their varying effects on the symptoms of schizophrenia, yet 20% to 60% of patients with schizophrenia are considered treatment-resistant. While clozapine has been shown to be the most effective antipsychotic, negative symptoms commonly persist in clozapine-treated patients. Research shows that oxytocin has neuromodulatory effects on social perception and also enhances empathy and attentional engagement in individuals with schizophrenia, suggesting it has therapeutic effects on negative symptoms. The present study presents a series of cases suggesting the efficacy of combining clozapine and oxytocin for the reduction of positive and negative symptoms. This work contributes to schizophrenia treatment research by reporting a novel, integrated pharmacological approach to treatment-resistant schizophrenia. Methods: Retrospective chart reviews were conducted on the charts of 15 patients with treatment-resistant schizophrenia. The patients were all admitted to the persistent psychotic disorder unit at a private hospital between May 2014 and September 2017. The average treatment duration was 2.7 months with a range between 1 and 9 months. All patients were 18 years or older and met the DSM-5 criteria for schizophrenia. The Positive and Negative Syndrome Scale (PANSS) was used to assess the efficacy of the combination treatment. Clozapine was prescribed to all 15 patients after they had failed to improve in three different trials of other antipsychotic medications. Intranasal oxytocin (10 IU 2x per day; 20 IU 3x per day) was prescribed to 11 of the patients only after the improvement in positive symptoms on the PANSS with clozapine had plateaued. Due to the risk of intranasal substance use in all the patients, oxytocin was administered sublingually to ensure adequate and less variable absorption of the neuropeptide. Results: Over the course of treatment, PANSS scores reflected significant changes (p <. 001) from admission until the introduction of oxytocin. The overall average PANSS score on admission was 125; after stabilization on clozapine, the average score decreased to 71. Following oxytocin administration (8 weeks), the average score decreased further to 52. Clinical and family notes indicated clinically meaningful improvements in affect, eye contact, and ability to socialize. Discussion: The combined effect of sublingual oxytocin and clozapine resulted in marked improvements for individuals with previously treatment-resistant symptoms. Though each patient benefitted from clozapine alone, negative symptoms persisted. Once oxytocin was administered, negative symptoms were reduced to the extent that patients, their families, and treatment program staff all observed a significant reduction in the patients' anxiety and an improvement in the patients' relatedness. Moreover, 11 of the 15 patients were able to return to school and/or work. While this case series cannot establish that oxytocin is responsible for the clinical improvements seen here, it does suggest that it may improve negative symptoms and social functioning in patients with treatment-resistant schizophrenia showing incomplete improvement with clozapine alone. The present study suggests the need for future research to explore the possibility that oxytocin can mitigate the negative symptoms of schizophrenia.